Hak dan Tanggung Jawab Anak dalam Perdata Islam - Noer Zaini Khalis; Faisar Ananda (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
Children are a trust from Allah SWT, occupying a significant role in familial and societal life. In Islamic civil law, children are considered legal entities with rights and obligations that need safeguarding and fulfillment. This research seeks to elucidate the rights of children under Islamic civil law, the obligations of children to their parents, and the legal frameworks governing children in the Compilation of Islamic Law and statutory law in Indonesia. The used study methodology is normative legal research, using both a statutory and a conceptual approach. The study's findings demonstrate that children possess the rights to lineage, nourishment, education, protection, and inheritance. Furthermore, children have the obligation to be dedicated, respectful, supportive, and to pray for their parents. The safeguarding of children's rights is governed by the Qur'an, hadith, the Compilation of Islamic Law, and the Child Protection Law. Consequently, the equilibrium between children's rights and obligations serves as a fundamental foundation for establishing a peaceful family in accordance with the norms of Islamic Sharia..